Impact of COVID-19 on U.S. Hospital-Based Injury Prevention Professionals: A National Survey. Issue 1 (January 2023) - Edwards, Courtney; Arabian, Sandra Strack; Colburn-Hargis, Paige; Duchossois, Gina; Adams, Christy
Abstract : Background: COVID-19 challenged U.S. trauma centers to grapple with demands for expanded services with finite resources while also experiencing a concurrent increase in violent injuries. Objective: The purpose of this study was to describe the impact of COVID-19 on the roles and duties of U.S. hospital-based injury prevention professionals. Methods: This descriptive cross-sectional survey study of hospital-based injury prevention professionals was conducted between June 2021 and August 2021. Participants were recruited from six organizational members of the national Trauma Prevention Coalition, including the American Trauma Society, Emergency Nurses Association, Injury Free Coalition for Kids, Safe States Alliance, Society for Trauma Nurses, and Trauma Center Association of America. Results were analyzed using descriptive and inferential statistics. Results: A total of 216 participants affiliated with 227 trauma centers responded. The following changes were reported during 2020: change in injury prevention position (range = 31%–88%); change in duties (range = 92%–100%); and change to hospital-based injury prevention programs (range = 75%–100%). Sixty-one (43%) single-center participants with a registered nurse license were reassigned to clinical duties compared with six (10%) nonlicensed participants (OR = 5.6; 95% CI [1.96, 13.57]; p < .001). Injury prevention programs at adult-only and combined adult and pediatric trauma centers had higher odds of suspension than pediatric-only trauma centers (OR = 3.6; 95% CI [1.26, 10.65]; p < .017). Conclusion: The COVID-19 response exposed the persistent inequity and limited prioritization of injury prevention programming as a key deliverable for trauma centers.